First-line chemotherapy with tislelizumab for patients with extensive-stage small cell lung cancer: a cost-effectiveness analysis - Rong Long; Fangping Chen (Scientific Reports)
Abstract The Phase 3 RATIONALE-312 trial (NCT04005716) showed that tislelizumab plus chemotherapy led to a noteworthy enhancement resulted in a significant improvement in overall survival among patients diagnosed with extensive-stage small-cell lung cancer (ES-SCLC) compared to chemotherapy alone. The treatment also had an acceptable level of safety. Nevertheless, the debate over the efficacy of implementing several treatment plans in competition continues due to the significant expenses involved. Therefore, we aimed to evaluate the potential efficacy and cost of tislelizumab treatment as a first-line treatment for the ES-SCLC patient population in China. The study assessed primary health outcomes by measuring life years (LYs), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). This was done using a Markov model considering three health states with a 15-year horizon. To assess its model resilience, we conducted one-way sensitivity analyses with probability. In addition, subgroup analyses of some pre-specified patients was performed. Compared to chemotherapy alone, tislelizumab plus chemotherapy resulted in an additional 0.34 ($8,028) QALYs, leading to an ICER of $23,553 per QALY for the overall patient population. The ICER was lower than the assumed willingness-to-pay threshold of $35,367 per QALY. Approximately 60% of simulations suggested that tislelizumab in combination with chemotherapy was cost-effective, while 40% suggested that chemotherapy alone was cost-effective. The subsequent sensitivity analyses revealed that the health utility value associated with the disease progression parameter had the greatest influence on ICER. Tislelizumab plus chemotherapy was a preferable treatment option for regimens for patients with ES-SCLC in China. This finding is important in guiding the Chinese healthcare system.